A flexible memristor and a preparation method thereof
Patent Information
- Application Number
- CN202510937755.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-08
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2045-07-08
AI Technical Summary
[0004]基于上述现有技术的不足,本发明的目的在于提供一种柔性忆阻器及其制备方法,旨在解决现有柔性忆阻器所存在的电导调控不稳定、机械变形下性能衰减的问题
[0028]有益效果:本发明中柔性忆阻器采用具有有序层状结构和规则孔隙的二维π共轭金属有机框架材料作为阻变层材料,在外加电场作用下,二维π共轭金属有机框架材料中发生可控的电子/离子捕获与释放行为,可实现稳定的易失性电阻状态切换。与依赖导电丝机制的传统柔性忆阻器相比,本发明提供的基于二维π共轭金属有机框架材料的柔性忆阻器由于不依赖导电丝机制,而是依赖二维π共轭金属有机框架材料中发生可控的电子/离子捕获与释放,更具可逆性和稳定性,且受应力扰动影响较小,在机械弯折条件下具有良好的循环耐久性和机械可靠性。因此,本发明提供的柔性忆阻器在保持良好柔性的同时,实现了低功耗、高导通比和优异的电学稳定性,适用于可穿戴电子、柔性神经形态计算系统等新兴应用领域。
Smart Images

Figure CN121001562B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electronic device technology, and in particular to a flexible memristor and its fabrication method. Background Technology
[0002] In the traditional von Neumann architecture, the physical separation of computation and storage leads to bottlenecks such as low energy efficiency and high latency, making it difficult to meet the demands of the Internet of Things (IoT) era for real-time aggregation and efficient processing of massive amounts of sensor data. In contrast, the human brain, through its event-driven parallel mechanism, achieves billions of calculations per second with a power consumption of only about 20 watts, providing a bio-inspired path to overcome the "von Neumann bottleneck." Neuromorphic computing, through its in-memory computing mechanism that simulates synapses, has developed key devices including memristors and neural transistors. Among them, memristors have unique advantages in in-memory computing due to their simple structure (two electrodes), femtojoule-level power consumption, and high compatibility with complementary metal-oxide-semiconductor (CMOS) processes. Furthermore, volatile memristors, which can automatically recover to their initial state after the external voltage is removed, have advantages such as fast response and low power consumption. They have been used to develop high-efficiency memories and construct neuromorphic computing systems, and can also be used in the development of static / dynamic random access memories (SRAM, DRAM), artificial neurons, etc. Vector-matrix multiplication based on memristor cross-arrays can achieve energy efficiency hundreds of times higher than traditional systems, and its nanosecond-level switching characteristics also support large-scale, high-density integration, making it particularly suitable for parallel task processing in convolutional neural networks. With the rise of flexible electronics, flexible memristors have shown great potential in applications such as wearable devices, implantable bioelectronics, and curved surface sensing systems. However, existing flexible memristors still face several challenges in practical applications, including unstable conductance control and performance degradation under mechanical deformation.
[0003] Therefore, existing technologies still need to be improved and developed. Summary of the Invention
[0004] In view of the shortcomings of the prior art, the purpose of this invention is to provide a flexible memristor and its preparation method, which aims to solve the problems of unstable conductance control and performance degradation under mechanical deformation of existing flexible memristors.
[0005] The technical solution of the present invention is as follows:
[0006] In a first aspect, the present invention provides a flexible memristor, wherein the flexible memristor comprises a flexible substrate, a bottom electrode, a resistive switching layer, and a top electrode stacked sequentially, the resistive switching layer comprising a two-dimensional π-conjugated metal-organic framework material, the two-dimensional π-conjugated metal-organic framework material being formed by coordination between metal ions and organic ligands; the metal ions comprising at least one of nickel ions, copper ions, cobalt ions, zinc ions, and iron ions; the organic ligands comprising at least one of 2,3,6,7,10,11-hexahydroxytriphenyl, hexaaminotriphenyl, tetracarboxyporphyrin, and tetrahydroxyporphyrin.
[0007] Optionally, the two-dimensional π-conjugated metal-organic framework material is formed by coordination of nickel ions with 2,3,6,7,10,11-hexahydroxytriphenyl.
[0008] Optionally, the flexible substrate includes one of polyethylene terephthalate flexible substrate, polyimide flexible substrate, polyethylene naphthalate flexible substrate, and polydimethylsiloxane flexible substrate.
[0009] Optionally, the bottom electrode comprises at least one of indium tin oxide, gold, silver, aluminum, carbon nanotubes, and conductive polymer materials.
[0010] Optionally, the top electrode comprises at least one of indium tin oxide, gold, silver, aluminum, carbon nanotubes, and conductive polymer materials.
[0011] A second aspect of the present invention provides a method for fabricating the flexible memristor described above, comprising the following steps:
[0012] Provide a flexible substrate with a bottom electrode on its surface;
[0013] A resistive switching layer is formed on the bottom electrode;
[0014] A top electrode is formed on the resistive switching layer.
[0015] Optionally, a resistive switching layer is formed on the bottom electrode by one of the following methods: interfacial self-assembly, solvothermal method, hydrothermal method, surfactant-assisted crystallization method, liquid phase deposition method, and slow-release reaction method.
[0016] Optionally, the step of forming a resistive switching layer on the bottom electrode specifically includes:
[0017] Organic ligands are added to water to obtain an organic ligand solution;
[0018] Metal salts are added to water, and the pH of the system is adjusted to a preset value to obtain a metal salt solution.
[0019] The metal salt solution is added to the organic ligand solution, and the reaction is carried out under stirring for a first preset time to obtain a colloidal suspension;
[0020] A flexible substrate with a bottom electrode on its surface is placed on the gas-liquid interface of the colloidal suspension, and the bottom electrode is made to adhere to the gas-liquid interface. After standing for a second preset time, it is taken out and annealed to form a resistive switching layer on the bottom electrode.
[0021] Optionally, the step of forming a resistive switching layer on the bottom electrode specifically includes:
[0022] 2,3,6,7,10,11-hexahydroxytriphenyl was added to water to obtain an organic ligand solution;
[0023] Nickel salts were added to water, then ammonia was added and the pH of the system was adjusted to 8.0±0.5 to obtain a metal salt solution.
[0024] The metal salt solution was added to the organic ligand solution, and the mixture was stirred at 500-800 rpm for 30 min to obtain a colloidal suspension.
[0025] A flexible substrate with a bottom electrode on its surface is placed on the gas-liquid interface of the colloidal suspension, and the bottom electrode is made to adhere to the gas-liquid interface. After standing for 30 minutes, it is taken out and annealed at a temperature of 90-100°C for 1 hour to form a resistive switching layer on the bottom electrode.
[0026] Optionally, a bottom electrode is formed on a flexible substrate using one of the following methods: thermal evaporation, magnetron sputtering, electron beam evaporation, printing transfer, and laser ablation, to obtain a flexible substrate with a bottom electrode on its surface; and / or,
[0027] A top electrode is formed on the resistive switching layer by one of the following methods: thermal evaporation, magnetron sputtering, electron beam evaporation, printing transfer, and laser ablation.
[0028] Beneficial Effects: The flexible memristor in this invention uses a two-dimensional π-conjugated metal-organic framework (MOF) material with an ordered layered structure and regular pores as the resistive switching layer material. Under the action of an external electric field, controllable electron / ion capture and release behavior occurs in the two-dimensional π-conjugated MOF material, enabling stable volatile resistance state switching. Compared with traditional flexible memristors that rely on conductive filament mechanisms, the flexible memristor based on two-dimensional π-conjugated MOF material provided by this invention is more reversible and stable because it does not rely on conductive filament mechanisms but on controllable electron / ion capture and release within the two-dimensional π-conjugated MOF material. It is also less affected by stress disturbances and exhibits good cycle durability and mechanical reliability under mechanical bending conditions. Therefore, the flexible memristor provided by this invention achieves low power consumption, high conduction ratio, and excellent electrical stability while maintaining good flexibility, making it suitable for emerging application fields such as wearable electronics and flexible neuromorphic computing systems. Attached Figure Description
[0029] Figure 1 This is a schematic diagram of the synthesis of Ni-HHTP.
[0030] Figure 2 This is a schematic diagram of the flexible memristor in Example 1.
[0031] Figure 3 This is a schematic diagram of the preparation of the Ni-HHTP thin film in Example 1.
[0032] Figure 4 The image shows the PXRD results of the Ni-HHTP thin film in Example 1.
[0033] Figure 5 The image shows the FTIR results of the Ni-HHTP thin film in Example 1.
[0034] Figure 6 This is a current-voltage curve of the flexible memristor in Example 1 under the conditions of bending, stretching, and compression.
[0035] Figure 7 The graph shows the switching ratio and threshold voltage changes of the flexible memristor in Example 1 after 1000 bending cycles. Detailed Implementation
[0036] This invention provides a flexible memristor and its fabrication method. To make the objectives, technical solutions, and effects of this invention clearer and more explicit, the invention is further described in detail below. It should be understood that the specific embodiments described herein are only for explaining the invention and are not intended to limit the invention.
[0037] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used in this specification is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention.
[0038] The terms used in this document, such as “vertical,” “horizontal,” “up,” “down,” “left,” “right,” and similar expressions, are for illustrative purposes only and do not represent the only possible implementation.
[0039] In this invention, unless otherwise explicitly specified and limited, "above" or "below" the second feature can mean that the first feature is in direct contact with the second feature, or that the first feature is in indirect contact with the second feature through an intermediate medium. Furthermore, "above," "over," and "on top" of the second feature can mean that the first feature is directly above or diagonally above the second feature, or simply that the first feature is at a higher horizontal level than the second feature. "Below," "below," and "under" the second feature can mean that the first feature is directly below or diagonally below the second feature, or simply that the first feature is at a lower horizontal level than the second feature.
[0040] If the embodiments of the present invention involve descriptions such as "first" or "second", such descriptions are for descriptive purposes only and should not be construed as indicating or implying their relative importance or implicitly specifying the number of technical features indicated.
[0041] Traditional flexible memristors often employ inorganic oxides or polymer materials, relying on the formation / breakage mechanism of conductive filaments for resistance switching. However, under the influence of material pore structure, interfacial stress, or bending deformation, carrier paths can become unstable, electrode interfaces can degrade, or conduction channels can break, leading to conduction state drift and decreased cycling performance. Therefore, existing flexible memristors generally suffer from unstable conductance control and performance degradation under mechanical bending conditions. Based on this, the inventors studied metal-organic framework (MOF) materials and found that MOF materials have the following advantages: (1) ultra-high specific surface area and porous structure containing active groups provide abundant active sites for interfacial reactions and ion migration; (2) the high tunability of metal nodes and ligand combinations makes their crystal structure, band structure and ion migration barrier designable; (3) uniform and tunable permanent pore size helps to construct efficient ion channels; (4) the layered structure can achieve precise thickness control through liquid phase method, and the porous structure can form geometric constraints on ion channels, thereby improving the uniformity of resistance switching; (5) it also has excellent mechanical flexibility and large-area film formation capability. The inventors believe that these characteristics make it an ideal material platform for realizing high-density, low-power flexible neuromorphic devices. At the same time, in order to meet the comprehensive requirements of flexible memristors, in-depth research is still needed in areas such as interface engineering, environmental stability improvement and device structure optimization. How to achieve structure-performance-device coupling regulation of MOF materials has become a key scientific issue to promote its practical application in the field of flexible neuromorphic electronics. Therefore, embodiments of the present invention provide a flexible memristor, wherein the flexible memristor includes a flexible substrate, a bottom electrode, a resistive switching layer, and a top electrode stacked sequentially. The resistive switching layer includes a two-dimensional π-conjugated MOF material, which is formed by coordination between metal ions and organic ligands. The metal ions include at least one selected from nickel ions, copper ions, cobalt ions, zinc ions, and iron ions. The organic ligands include at least one selected from 2,3,6,7,10,11-hexahydroxytriphenyl (HHTP), hexaaminotriphenyl (HITP), tetracarboxyporphyrin (H2TCPP), and tetrahydroxyporphyrin. That is, the two-dimensional π-conjugated MOF material uses at least one selected from nickel ions, copper ions, cobalt ions, zinc ions, and iron ions as metal nodes, and at least one selected from 2,3,6,7,10,11-hexahydroxytriphenyl, hexaaminotriphenyl, tetracarboxyporphyrin, and tetrahydroxyporphyrin as organic ligands.
[0042] In this embodiment of the invention, the flexible memristor uses a two-dimensional π-conjugated MOF material with an ordered layered structure and regular pores as the resistive switching layer material. Under the action of an external electric field, controllable electron / ion capture and release behavior occurs in the two-dimensional π-conjugated MOF material, achieving stable volatile resistance state switching. Compared with traditional memristors that rely on conductive filament mechanisms, the flexible memristor based on two-dimensional π-conjugated MOF material provided by this invention is more reversible and stable because it does not rely on conductive filament mechanisms but on controllable electron / ion capture and release in the two-dimensional π-conjugated MOF material. It is also less affected by stress disturbances and exhibits good cycle durability and mechanical reliability under mechanical bending conditions. Therefore, the flexible memristor provided by this embodiment of the invention achieves low power consumption, high conduction ratio, and excellent electrical stability while maintaining good flexibility, making it suitable for emerging application fields such as wearable electronics and flexible neuromorphic computing systems.
[0043] In some embodiments, the two-dimensional π-conjugated MOF material is formed by the coordination of nickel ions with 2,3,6,7,10,11-hexahydroxytriphenyl (e.g., Figure 1 (As shown).
[0044] This two-dimensional π-conjugated MOF material is used as the resistive switching layer material for flexible memristors, enabling the flexible memristors to achieve volatile resistive switching characteristics with good uniformity and high on / off ratio. It allows for stable conductance control and ensures that the flexible memristors maintain stable switching performance after multiple bending cycles, demonstrating excellent flexibility and reliability.
[0045] In some embodiments, the flexible substrate includes one of polyethylene terephthalate (PET) flexible substrate, polyimide (PI) flexible substrate, polyethylene naphthalate (PEN) flexible substrate, and polydimethylsiloxane (PDMS) flexible substrate.
[0046] In some embodiments, the bottom electrode includes at least one of indium tin oxide, gold, silver, aluminum, carbon nanotubes, and conductive polymer materials, but is not limited thereto.
[0047] In some embodiments, the top electrode comprises at least one of indium tin oxide, gold, silver, aluminum, carbon nanotubes, and conductive polymer materials, but is not limited thereto.
[0048] In some embodiments, the top electrode is a gold electrode. Compared with active metals such as silver, the use of a gold electrode effectively avoids the risk of migration and failure of active metals such as silver under operating voltage, thereby improving the stability and integration reliability of the flexible memristor.
[0049] This invention also provides a method for fabricating the flexible memristor described above, comprising the following steps:
[0050] S1. Provide a flexible substrate with a bottom electrode on its surface;
[0051] S2. A resistive switching layer is formed on the bottom electrode;
[0052] S3. A top electrode is formed on the resistive switching layer.
[0053] The fabrication method provided by this invention is simple, and the resulting flexible memristor exhibits volatile resistance switching characteristics, demonstrates good threshold switching behavior, and possesses excellent mechanical reliability and durability. This flexible memristor maintains stable switching performance even after multiple bending cycles, exhibiting excellent flexibility and reliability.
[0054] In step S1, in some embodiments, a bottom electrode is formed on a flexible substrate by means of one of the following methods, including but not limited to thermal evaporation, magnetron sputtering, electron beam evaporation, printing transfer, and laser ablation, to obtain a flexible substrate with a bottom electrode on its surface.
[0055] In step S2, in some embodiments, a resistive switching layer is formed on the bottom electrode by means of one of the following methods, including but not limited to interface self-assembly, solvothermal method, hydrothermal method, surfactant-assisted crystallization method, liquid phase deposition method and slow-release reaction method.
[0056] In some embodiments, the step of forming a resistive switching layer on the bottom electrode specifically includes:
[0057] S21. Add the organic ligand to water to obtain an organic ligand solution;
[0058] S22. Add the metal salt to the water, adjust the pH of the system to the preset value, and obtain the metal salt solution;
[0059] S23. The metal salt solution is added to the organic ligand solution, and the reaction is carried out under stirring for a first preset time to obtain a colloidal suspension;
[0060] S24. Place the flexible substrate with the bottom electrode on the surface on the gas-liquid interface of the colloidal suspension, and make the bottom electrode adhere to the gas-liquid interface. After standing for a second preset time, take it out and anneal it to form a resistive switching layer on the bottom electrode.
[0061] In this embodiment, MOF thin films are grown in situ on a flexible substrate with a bottom electrode on the surface using an interface self-assembly method to form a continuous and dense resistive switching layer.
[0062] In some specific embodiments, the step of forming a resistive switching layer on the bottom electrode specifically includes:
[0063] 2,3,6,7,10,11-hexahydroxytriphenyl was added to water to obtain an organic ligand solution;
[0064] Add a nickel salt (e.g., nickel acetate tetrahydrate, i.e., Ni(OAc)2·4H2O) to water, then add ammonia and adjust the pH of the system to 8.0±0.5 (to promote the deprotonation of 2,3,6,7,10,11-hexahydroxytriphenyl and the ordered assembly of MOF materials) to obtain a metal salt solution;
[0065] The metal salt solution is added to the organic ligand solution, and the mixture is stirred at 500-800 rpm (e.g., 500 rpm, 600 rpm, 700 rpm, or 800 rpm) for 30 min to obtain a colloidal suspension.
[0066] A flexible substrate with a bottom electrode on its surface is placed on the gas-liquid interface of the colloidal suspension, with the bottom electrode adhering to the gas-liquid interface. After standing for 30 minutes, it is removed and annealed at a temperature of 90-100℃ (e.g., 90℃, 92℃, 95℃, 98℃, or 100℃) for 1 hour. A two-dimensional π-conjugated MOF material film (denoted as Ni-HHTP film), also known as a resistive switching layer, is formed on the bottom electrode, with nickel ions as metal nodes and 2,3,6,7,10,11-hexahydroxytriphenyl as organic ligand.
[0067] In this embodiment, a continuous and uniform Ni-HHTP thin film is prepared in situ on a flexible substrate containing a bottom electrode on the surface using an interface self-assembly method, which is suitable for the fabrication of flexible memristors.
[0068] In some embodiments, the molar ratio of the nickel salt to the organic ligand is (1.5 to 2.5):1, for example, it can be 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1, 2.0:1, 2.1:1, 2.2:1, 2.3:1, 2.4:1 or 2.5:1, etc.
[0069] In this embodiment, a Ni-HHTP thin film is prepared on a flexible substrate by an interface self-assembly method to obtain a continuous and dense resistive switching layer.
[0070] In step S3, in some embodiments, a top electrode is formed on the resistive switching layer by one of the following methods: thermal evaporation, magnetron sputtering, electron beam evaporation, printing transfer, and laser ablation.
[0071] The present invention will be further described below through specific embodiments.
[0072] Example 1
[0073] This embodiment provides a flexible memristor and its fabrication method, wherein, as shown in the example... Figure 2As shown, the flexible memristor includes a flexible substrate, a bottom electrode, a Ni-HHTP thin film, and a top electrode stacked sequentially. The flexible substrate is a polyethylene terephthalate flexible substrate, the bottom electrode is an indium tin oxide (ITO) electrode, and the top electrode is a gold electrode.
[0074] like Figure 3 As shown, the fabrication method of the flexible memristor includes the following steps:
[0075] A flexible polyethylene terephthalate substrate (dimensions: length × width × thickness 2mm × 2mm × 0.188mm) with a pre-fabricated ITO electrode (thickness 185nm) was selected. The substrate was ultrasonically cleaned, dried with nitrogen, and treated with ultraviolet ozone to enhance surface hydrophilicity and film adhesion.
[0076] Dissolve 0.0175 g of 2,3,6,7,10,11-hexahydroxytriphenyl in 40 mL of deionized water to obtain an organic ligand solution.
[0077] Dissolve 0.0300 g of Ni(OAc)2·4H2O in 40 mL of deionized water, and slowly add ammonia to adjust the pH of the system to 8.0 to obtain a nickel salt solution.
[0078] The nickel salt solution was slowly added to the organic ligand solution, and the mixture was reacted for 30 minutes under magnetic stirring at 500 rpm to obtain a uniform dark purple colloidal suspension.
[0079] The aforementioned flexible polyethylene terephthalate substrate with ITO electrodes on its surface was inverted and suspended at room temperature (25°C) on the gas-liquid interface of a dark purple colloidal suspension (i.e., the ITO electrodes were attached to the gas-liquid interface), and kept still for 30 min. At the interface, the Ni-HHTP film self-assembled through coordination, eventually depositing as a continuous MOF film at the air / water interface. After removing the flexible polyethylene terephthalate substrate with the MOF film and ITO electrodes from the solution, it was rinsed alternately with ethanol and deionized water to remove surface impurities, then dried in a nitrogen stream, and annealed at 90°C for 1 h to improve the crystallinity and stability of the film, thus obtaining a Ni-HHTP film (approximately 40 nm thick).
[0080] The structure and chemical composition of the Ni-HHTP thin film were analyzed, mainly using powder X-ray diffraction (PXRD) and Fourier transform infrared spectroscopy (FTIR). The PXRD results are shown in the figure below. Figure 4 As shown, the FTIR results are plotted as follows. Figure 5As shown in the PXRD results, obvious diffraction peaks are present at 2θ = 9.5°, 13.8°, and 16.4°, corresponding to the (110), (130), and (201) crystal planes, respectively. A strong peak also appears at 2θ = 26.8°, belonging to the (002) crystal plane, indicating that the material possesses a typical layered structure and π-π stacking characteristics. In the FTIR results, a peak appears at 3014 cm⁻¹. -1 and 1205cm -1 The stretching vibration peaks of OH and CO, 1413 cm⁻¹ -1 The C=C skeleton vibration peak, and the 780-900 cm⁻¹ peak. -1 CH bending vibration, 670cm -1 Ni-O (metal and water) vibration and 543 cm -1 The Ni-O (metal and ligand) coordination peaks are consistent with the structural characteristics of Ni-HHTP thin films in the literature.
[0081] A flexible memristor was obtained by depositing a 50 nm thick gold electrode on a Ni-HHTP thin film using a metal mask and thermal evaporation process.
[0082] The electrical performance and stability of the flexible memristor under mechanical deformation conditions were tested. Specifically, a semiconductor parameter analyzer was used to test the current-voltage characteristics of the flexible memristor in a bidirectional voltage scan mode (0→+2V→0) to record the response curve of current as a function of voltage. During the test, the conductivity behavior of the flexible memristor was compared in three states: undeformed (flat), stretched, and compressed. The stretched and compressed states were achieved by fixing the flexible memristor to convex (outer bend) and concave (inner bend) arc molds with a radius of curvature of approximately 1 cm, respectively. The outer bend mold subjected the device surface to tensile strain, while the inner bend mold subjected the device surface to compressive strain. The results are as follows: Figure 6 As shown, the device exhibits typical volatile resistance switching characteristics in all three states: when the applied voltage exceeds the positive threshold voltage, the current rapidly transitions to the low resistance state (LRS); and when the voltage falls back below the holding voltage, the device automatically returns to the high resistance state (HRS), demonstrating good threshold switching behavior.
[0083] Furthermore, to evaluate the electrical stability of the flexible memristor in Example 1 under long-term mechanical stress, it was subjected to multiple bending cycle tests. During the test, the flexible memristor was fixed on a cylindrical mold with a radius of curvature of 1 cm and repeatedly bent and unfolded. The maximum number of cycles was set to 1000. The on / off ratio (current ratio of LRS to HRS) and the forward threshold voltage were recorded every 100 cycles. The results are as follows: Figure 7As shown, the results indicate that the device maintains stable on / off characteristics throughout the continuous bending process, with no significant attenuation in the on / off ratio and threshold voltage. This demonstrates that the flexible memristor possesses excellent mechanical reliability and durability, a compact overall structure, and good bending compliance, making it suitable for applications requiring high mechanical stability, such as wearable or implantable neuromorphic electronic devices.
[0084] In summary, this invention provides a flexible memristor and its fabrication method. The flexible memristor utilizes a two-dimensional π-conjugated metal-organic framework (MOF) material with an ordered layered structure and regular pores as the resistive switching layer. Under an applied electric field, controllable electron / ion capture and release behavior occurs within the MOF material, enabling stable volatile resistance state switching. Compared to traditional flexible memristors that rely on conductive filament mechanisms, the flexible memristor based on the two-dimensional π-conjugated MOF material provided by this invention, because it does not rely on conductive filament mechanisms but rather on controllable electron / ion capture and release within the MOF material, exhibits greater reversibility and stability, and is less affected by stress disturbances. It also demonstrates good cycle durability and mechanical reliability under mechanical bending conditions. Therefore, the flexible memristor provided by this invention achieves low power consumption, high conduction ratio, and excellent electrical stability while maintaining good flexibility, making it suitable for emerging application areas such as wearable electronics and flexible neuromorphic computing systems.
[0085] It should be understood that the application of the present invention is not limited to the examples above. Those skilled in the art can make improvements or modifications based on the above description, and all such improvements and modifications should fall within the protection scope of the appended claims.
Claims
1. A flexible memristor, characterized in that, The flexible memristor comprises a flexible substrate, a bottom electrode, a resistive switching layer, and a top electrode stacked sequentially. The resistive switching layer is composed of a two-dimensional π-conjugated metal-organic framework material. The two-dimensional π-conjugated metal-organic framework material is formed by the coordination of nickel ions with 2,3,6,7,10,11-hexahydroxytriphenyl. The top electrode is a gold electrode; Under the action of an external electric field, the flexible memristor achieves volatile resistance state switching through the controllable electron capture and release behavior in the two-dimensional π-conjugated metal-organic framework material.
2. The flexible memristor according to claim 1, characterized in that, The flexible substrate includes one of polyethylene terephthalate flexible substrate, polyimide flexible substrate, polyethylene naphthalate flexible substrate, and polydimethylsiloxane flexible substrate.
3. The flexible memristor according to claim 1, characterized in that, The bottom electrode includes at least one of indium tin oxide, gold, silver, aluminum, carbon nanotubes, and conductive polymer materials.
4. A method for fabricating a flexible memristor according to any one of claims 1-3, characterized in that, Includes the following steps: Provide a flexible substrate with a bottom electrode on its surface; A resistive switching layer is formed on the bottom electrode; A top electrode is formed on the resistive switching layer.
5. The preparation method according to claim 4, characterized in that, A resistive switching layer is formed on the bottom electrode using one of the following methods: interfacial self-assembly, solvothermal method, hydrothermal method, surfactant-assisted crystallization method, liquid phase deposition method, and slow-release reaction method.
6. The preparation method according to claim 4, characterized in that, The step of forming a resistive switching layer on the bottom electrode specifically includes: Organic ligands are added to water to obtain an organic ligand solution; Metal salts are added to water, and the pH of the system is adjusted to a preset value to obtain a metal salt solution. The metal salt solution is added to the organic ligand solution, and the reaction is carried out under stirring for a first preset time to obtain a colloidal suspension; A flexible substrate with a bottom electrode on its surface is placed on the gas-liquid interface of the colloidal suspension, and the bottom electrode is made to adhere to the gas-liquid interface. After standing for a second preset time, it is taken out and annealed to form a resistive switching layer on the bottom electrode.
7. The preparation method according to claim 4, characterized in that, The step of forming a resistive switching layer on the bottom electrode specifically includes: 2,3,6,7,10,11-hexahydroxytriphenyl was added to water to obtain an organic ligand solution; Nickel salts were added to water, then ammonia was added and the pH of the system was adjusted to 8.0 ± 0.5 to obtain a metal salt solution. The metal salt solution was added to the organic ligand solution, and the mixture was stirred at 500-800 rpm for 30 min to obtain a colloidal suspension. A flexible substrate with a bottom electrode on its surface is placed on the gas-liquid interface of the colloidal suspension, and the bottom electrode is made to adhere to the gas-liquid interface. After standing for 30 minutes, it is taken out and annealed at a temperature of 90~100 °C for 1 hour to form a resistive switching layer on the bottom electrode.
8. The preparation method according to claim 4, characterized in that, A bottom electrode is formed on a flexible substrate using one of the following methods: thermal evaporation, magnetron sputtering, electron beam evaporation, printing transfer, and laser ablation, resulting in a flexible substrate with a bottom electrode on its surface; and / or, A top electrode is formed on the resistive switching layer by one of the following methods: thermal evaporation, magnetron sputtering, electron beam evaporation, printing transfer, and laser ablation.
Citation Information
Patent Citations
Field effect transistor based on Ni3 (HHTP) 2 conductive film and preparation method of filed effect transistor
CN113437219A